Plantation forestry in Brazil: The potential impacts of climatic change - Fearnside, Philip Martin (Biomass and Bioenergy, 1999)
Most climatic changes predicted to occur in Brazil would reduce yields of silvicultural plantations, mainly through increased frequency and severity of droughts brought on by global warming and by reduction of water vapor sources in Amazonia caused by deforestation. Some additional negative effects could result from changes in temperature, and positive effects could result from CO2 enrichment. The net effects would be negative, forcing the country to expand plantations onto less-productive land, requiring increased plantation area (and consequent economic losses) out of proportion to the climatic change itself. These impacts would affect carbon sequestration and storage consequences of any plans for subsidizing silviculture as a global warming mitigation option. Climate change can be expected to increase the area of plantations needed to supply projected internal demand for and exports of end products from Brazil. June-July-August (dry season) precipitation reductions indicated by simulations reported by the Intergovernmental Panel on Climate Change (IPCC) correspond to rainfall declines in this critical season of approximately 34% in Amazonia, 39% in Southern Brazil and 61% in the Northeast. As an example, if rainfall in Brazilian plantation areas (most of which are now in Southern Brazil) were to decline by 50%, the area needed in 2050 would expand by an estimated 38% over the constant climate case, bringing the total plantation area to 4.5 times the 1991 area. These large areas of additional plantations imply substantial social and environmental impacts. Further addition of plantation area as a global warming response option would augment these impacts, indicating the need for caution in evaluating carbon sequestration proposals.Most climatic changes predicted to occur in Brazil would reduce yields of silvicultural plantations, mainly through increased frequency and severity of droughts brought on by global warming and by reduction of water vapor sources in Amazonia caused by deforestation. Some additional negative effects could result from changes in temperature, and positive effects could result from CO2 enrichment. The net effects would be negative, forcing the country to expand plantations onto less-productive land, requiring increased plantation area out of proportion to the climatic change itself. These impacts would affect carbon sequestration and storage consequences of any plans for subsidizing silviculture as a global warming mitigation option.
Keywords: Climate Change; Drought Resistance; Environmental Impact Assessment; Greenhouse Effect; Water Vapor; Atmospheric Temperature; Carbon Dioxide; Drought; Environmental Impact; Global Warming; Deforestation; Silviculture; Forestry; Carbon Sequestration; Climate Change; Forestry Production; Plantation Forestry; Yield Response; Eucalyptus